VARIATION OF SEED PRODUCTION AND VIABILITY IN A FULL-SIB TRIAL OF Melaleuca cajuputi sub sp. cajuputi IN GUNUNGKIDUL YOGYAKARTA - Baskorowati, Liliana; Susanto, Mudji; Prasetyono, Prasetyono; Kartikawati, Noor; Rimbawanto, Anto (Indonesian Journal of Forestry Research, 2012)
Family variation of capsule production and the seed viability in the Paliyan full-sib trial of Melaleuca cajuputi subsp. cajuputi, at Gunungkidul, Yogyakarta, were observed. The full-sib trial was designed as Incomplete Block Design, consisting of 39 families; six individual as tree plot and replicated in eight blocks. Height and diameter at breast height were assessed to identify the correlation between capsule category and growth performance. The capsule production was assessed visually to one of the capsule categories: â0â for none; â1â for light; â2â for medium and â3â for heavy. Results showed that each family of M. cajuputi sub sp. cajuputi equally contributedÂ  to the seed production.Â Â  Progeny analysis showed that the seed productions were not strongly under genetic control (h2i) = 0.12. This study also found positive correlation between the flowering strength (the flower production levels) and the number of capsule (R2=0.279). However, there were no significant differences between the flowering levels and the viability of M. cajuputi sub sp. cajuputi. Mean seed viability was 31%,Â  there were no significantly differences of capsules production between trees having high flowering intensity and low flowering intensity. Low seed viability was assumed due to the unsynchronicity of flowering, leading to the low levels of outcrossing rate. Therefore, selection of families with synchronicity of flowering was recommended to establish a seed orchard.